Activation of NMDA receptors and the mechanism of inhibition by ifenprodil - Tajima, Nami (Nature, 2016)
The physiology of N-Methyl-D-aspartate (NMDA) receptors in mammals is fundamental to brain development and function. NMDA receptors are ionotropic glutamate receptors that function as heterotetramers composed mainly of GluN1 and GluN2 subunits. Activation of NMDA receptors requires binding of neurotransmitter agonists to a ligand-binding domain (LBD) and structural rearrangement of an amino terminal domain (ATD). Recent crystal structures of GluN1/GluN2B NMDA receptors in the presence of agonists and an allosteric inhibitor, ifenprodil, represent the allosterically inhibited state. However, how the ATD and LBD move to activate the NMDA receptor ion channel remains unclear. Here, we combine x-ray crystallography, single-particle electron cryomicroscopy, and electrophysiology to show that, in the absence of ifenprodil, the bi-lobed structure of GluN2 ATD adopts an open-conformation accompanied by rearrangement of the GluN1-GluN2 ATD heterodimeric interface, altering subunit orientation in the ATD and LBD and forming an active receptor conformation that gates the ion channel.